Probing the nature of peripheral boryl groups within luminescent tellurophenes. (30th November 2016) - Braun, Christina A.; Zomerman, Derek; de Aguiar, Inara; Qi, Yanyu; Delgado, William Torres; Ferguson, Michael J.; McDonald, Robert; de Souza, Gabriel L. C.; He, Gang; Brown, Alex; Rivard, Eric
Abstract : In this article our attempts to tune the color of luminescence within a new class of aggregation-induced emission (AIE) active tellurophenes is reported along with computational details that include spin–orbit coupling effects so as to better understand the nature of emission in the phosphorescent tellurophene (B-Te-6-B ). Despite not meeting some of the initial synthetic targets, the emission within a borylated tellurophene can be altered with the addition of an N-heterocyclic carbene.